Thermal improvement of the vertical plate-fin heat sink by variable fin thickness pattern and utilizing phase change material: A numerical investigation - Pourhemmati, Shayan; Hossainpour, Siamak (Journal of energy storage, 2023)
In this 3-D (three-dimensional) numerical study, variable fin thickness is proposed to address the thermal problem of the vertical plate-fin heat sink (PFHS) under natural convection. This design aims to facilitate heat transfer by preventing the merging of boundary layers and reducing the weight and cost of manufacturing. Simulations are carried out with COMSOL Multiphysics to solve continuity, momentum, and energy equations under a time-dependent condition. The PFHS with the dimension of 10 × 5.5 × 4.5 cm is hired with two fin convergence angles (α = 1.145, 0.572), and the number of fins and applied heat rate are varied from 4 to 7 and 2.5 W to 20 W, respectively. The numerical results show that the influence of the fin convergence angle on the thermal resistance rises by increasing fin numbers in the PFHS. The maximum reduction of 45.5 % is registered for thermal resistance in the highest density of fin numbers. Simulations are also expanded to study the PFHS under high temporary heat loads (40 and 80 W). For this, employing single and multiple PCMs for the thermal management of PFHS along with air cooling is proposed. The combined heat transfer mode results indicate that using PCM can decrease the critical temperature of PFHS by up to 8 %. Furthermore, the obtained result indicates that using multiple PCM with different melting temperatures is not advised for thermal management as it deters the full utilization of latent heat, and better performance achieves for a single PCM with a lower melting temperature. •A variable fin thickness for vertical PFHS is proposed to facilitate natural convection.•The new design offers a maximum of 45.5 % decrease in thermal resistance.•The PCM is utilized to neutralize hazardous temperatures in the junction of the PFHS.•The maximum temperature of the PFHS under transient heat load is reduced up to 8 % by using a single PCM.